PO.2.31 Different patterns of longitudinal changes in antinuclear antibodies titres in children with systemic lupus erythematosus. (27th September 2022) - Morán Álvarez, P; Bracaglia, C; Messia, V; Caiello, I; De Benedetti, F; Marasco, E
Abstract : Purpose to investigate the trend of antinuclear antibodies (ANA) and anti-dsDNA autoantibodies titers over time in children with a diagnosis of systemic lupus erythematosus (SLE). Methods: We enrolled 15 children with a diagnosis of SLE, fulfilling the SLICC criteria. For all patients included in the study ANA and anti-dsDNA antibodies testing was carried out from diagnosis every 3–4 months for 2 years. ANA were defined as negative for titers lower than 1:80. Laboratory parameters, clinical and demographic data was retrieved and analyzed. Statistical analysis was performed with software R_v. 4.0.3. Results: Following two years of follow-up, all patients had ANA titers significantly lower than at time of SLE diagnosis (Mann Whitney test, p=0.0002) ( figure 1A ). After two years of follow-up, 11 patients (73%) still had positive ANA (group 1), while 4 patients (26%) had negative ANA (group 0). At time of diagnosis no significant differences in ANA titers (Mann Whitney test, p=0.74) ( figure 1B ) nor in disease activity, as measured by SLEDAI, (Mann Whitney test, p=0.88) were observed ( table 1 ). No significant differences in organ involvement were observed ( table 1 ). Assessing the change over time in ANA titers, the 2 groups of patients showed two different patterns: in group 0, ANA titers quickly declined and disappeared in the first 6 months after diagnosis; in group 1, ANA titers declined more slowly, remaining positive at 2-year follow-up ( Figure 1C ). Both C3 and C4 increased in the follow-up period, with no different patterns between the 2 groups ( Figure 1C ). Similarly, anti-dsDNA antibodies titers declined over time with no clear different patterns between the 2 groups ( Figure 1C ). Conclusions: Our analysis showed two different patterns in the reduction of ANA titers over time in patients with childhood onset SLE, with 26% of patients becoming ANA negative after 6 months from diagnosis and remaining persistently negative during follow-up. Our data have important implications, specifically for the recruitment of patients into clinical trials, where the latest classification criteria of SLE require ANA positivity as entry criterion. Moreover, a seronegative state may represent a different subcategory of patients with SLE with specific pathogenetic pathways involved, possibly independently from autoantibodies. Therefore, further studies are needed to confirm and expand our data.